Participation of the armed forces in the disaster management system - Grozo Costa, Wolfang (2020)
This research aimed to determine whether the participation of the Armed Forces has contributed to the National Disaster Management System (Sinagerd). The research was correlational-applicative and the design was non-experimental. The population was made up of military personnel from the Armed Forces, who have participated in the El Niño phenomenon and in joint training, and comprised a total of 111 people; while, for the selection of the sample, the non-probabilistic type of sampling was used on a total of 86 people. The data collection techniques were documentary analysis and the survey; while the instrument used was the questionnaire, which obtained a positive value of 0.9187, with respect to Cronbach's Alpha coefficient, which proved its high reliability. For the validity study, experts' judgment was used, and they agreed that the instrument in question has a construct that allows measuring adequately the variables under study. For the analysis of results, descriptive statistics were used and to contrast the hypothesis, the chi-square technique was used. When applying this test, a value of 35,668 (X2 = 9,488) was obtained, so, with a significance level of 5%, the null hypothesis was rejected and the alternative hypothesis was accepted. Based on this, it was concluded that the participation of the Armed Forces has contributed significantly to the Disaster Risk Management System.